Teoretyczne uwarunkowania pomocy publicznej dla przedsiębiorców a pomoc publiczna w prawie UE - Augustyński, Iwo (Theoretical conditions of state aid vs state aid in European law, 2006)
In the paper two approaches to the analysis of the State aid are distinguished. One of them divides State aid in to two groups: offensive which aims to accomplish objectives of economic policy and a defensive one focusing on decreasing costs of economic changes. The other approach, derived directly from the analysis of different economic schools, justifies State aid by existence of such market occurrences which are not included in most of economic models such as market failures, public goods and external costs. In acquis communautaire, the issues concerning State aid are part of the competition policy, which is reserved for the European Commission. The analysis of the European law shows that the Commission allows for the State aid only when free competition fails. So it can be concluded that European regulations concerning State aid are based on these economic schools which pronounce for the limitation of State interventions in the economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 97-109